The role of fluid–structure interaction in pulsating bubble dynamics near a movable structure. (15th October 2021) - Hu, Zhen-Yu; Li, Shuai; Wang, Shi-Ping; Zhang, A-Man
Abstract: In the present study, the nonlinear bubble–plate interaction is investigated via boundary integral (BI) simulations with a particular focus on the effect of fluid–structure interaction (FSI). A series of experiments of electric discharge cavitation bubbles are also conducted to gain more physical insights. Good agreement between BI simulations and high-speed recordings is obtained. The effects of two geometrical parameters including the normalized stand-off distance γ and the plate-bubble size ratio θ (both scaled by the maximum bubble radius) are investigated systematically. We find four types of distinct bubble collapse patterns, namely, contacting jet that impacts the plate directly, non-contacting jet that impacts a layer of liquid, collision of two axial jets and no evident jet. A detailed phase diagram for the bubble collapse pattern is given in a large parameter space. Through the comparison of bubble dynamics near a movable and a fixed plate, the FSI effect is found to induce a significant increase in the jet impact velocity and the corresponding impact pressure. We also give a criterion condition for neglecting the FSI effect. Finally, we find two scaling laws for the plate motion with respect to γ, which can be explained using a semi-analytical model. Highlights: The transient fluid–structure interaction between a pulsating bubble and a movable plate is investigated. Four types of distinct bubble collapse patterns are identified in a large parameter space. The effect of FSI on the jet impact velocity and the structural pressure load is unveiled. A criterion condition for neglecting FSI effect is given. We find two scaling laws for the plate motion.